Pengaruh Corporate Social Responsibility (CSR) dan Return on Asset (ROA) pada Good Corporate Governance (GCG) - Nugrahani, Tri Siwi (Akmenika: Jurnal Akuntansi dan Manajemen, 2016)
This study aimed to examine the influence of social responsibility (Corporate Social Responssibility) and profitability (return on assets) on corporate governance (GCG). This study was performed on companies listed in the Stock Exchange in 2011-2013. Sampling method with purposive sampling and data collection methods with observation. This study tested with multiple regression analysis to test the hypothesis t test with significance of 5%.Hypothesis testing results show there is influence of CSR (Corporate Social Responsibility) in GCG with t test of 4.486 with 0.000 significance and ROA affect the GCG with t value of 2.160 with 0.036 significance. These results indicate that the hypothesis 1 and 2 are supported. The higher CSR undertaken by the company the higher the GCG companies, as well as higher profitability (ROA), the higher the GCG. Based on F test of 11.72 with a significance of 0,000 showed jointly between CSR and corporate governance affect the ROA. This suggests the hypothesis 3 is supported. which means jointly CSR and ROA effect on corporate governance. If CSR rose by 1 then GCG will rise 0054, as well as ROA rose by 1 it will increase the GCG of 0.015. Adjusted R2 value of 0.195 which demonstrates the ability of CSR (Corporate Social Responsibility) and profitability (ROA) can explain GCG amounted to 19.50%, while the remaining 80.50% is explained by other variables.